An Aggregate Biomarker Risk Score Predicts High Risk of Near‐Term Myocardial Infarction and Death: Findings From BARI 2D (Bypass Angioplasty Revascularization Investigation 2 Diabetes). Issue 7 (3rd July 2017) - Ghasemzadeh, Nima; Brooks, Maria M.; Vlachos, Helen; Hardison, Regina; Sikora, Sergey; Sperling, Laurence; Quyyumi, Arshed A.; Epstein, Stephen E.
Abstract : Background: In a previous study, we found that a biomarker risk score (BRS) comprised of C‐reactive protein, fibrin‐degradation products, and heat shock protein‐70 predicts risk of myocardial infarction and death in coronary artery disease patients. We sought to: (1) validate the BRS in the independent BARI 2D (Bypass Angioplasty Revascularization Investigation 2 Diabetes) cohort, (2) investigate whether 1 year of intensive medical therapy is associated with improved BRS, and (3) elucidate whether an altered BRS parallels altered risk. Methods and Results: Two thousand thirty‐two subjects with coronary artery disease were followed for 5.3±1.1 years for cardiovascular events. Biomarkers were measured at baseline and retested in 1304 subjects at 1 year. BRS was determined as the biomarker number above previously defined cut‐off values (C‐reactive protein >3 mg/L, heat shock protein‐70 >0.313 ng/mL, and fibrin‐degradation products >1 μg/mL). After adjustment for covariates, those with a BRS of 3 had a 4‐fold increased risk of all‐cause death and a 6.8‐fold increased risk of cardiac death compared with those with a BRS of 0 (95% CI, 2.9–16.0; P <0.0001). All individual biomarkers decreased by 1 year, with ≈80% of patients decreasing their BRS. BRS recalibrated at 1 year also predicted risk. Those with 1‐year BRS of 2 to 3 had a 4‐year mortality rate of 21.1% versus 7.4% for those with BRS of 0 to 1 ( P <0.0001). Conclusions: Our results validate the ability of the BRS to identify coronary artery disease patients at very high near‐term risk of myocardial infarction/death. After 1 year of intensive medical therapy, the BRS decreased significantly, and the reclassified BRS continued to track with risk. Our results suggest that repeated BRS measurements might be used to assess risk and recalibrate therapy.